COVID-19 Preventative Measures: Do-It-Yourself Cloth Face Coverings - Michelle D. Danyluk; Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman (EDIS)
This one-page full-color handout depicts essential components of face coverings for non-medical use and includes the following information: